Radionuclides content in grape molasses soil samples from Central Black Sea region of Turkey - Kurnaz, Aslı; Gezelge, Muazzez; Hançerlioğulları, Aybaba; Çetiner, M. Atıf; Turhan, Şeref (Informa UK Limited, 2016)
ABSTRACTThe activity concentrations of radionuclides in grape molasses soil samples collected from Zile (Tokat) plain in the Central Black Sea region of Turkey were measured by using gamma spectrometer with a NaI(Tl) detector. Also, the concentrations of 222Rn in soil samples and air were estimated essentially taking the activity concentrations of 226Ra measured in soil samples. Grape molasses soil samples with calcium carbonate content are used for sedimentation for making molasses in this region. The average activity concentrations of 232Th, 226Ra, 40K, and 137Cs were found as 62 ± 2, 68 ± 3, 479 ± 35, and 8.0 ± 0.3 Bq kg−1, respectively. The average concentrations of 222Rn in soil samples and air were estimated to be 50 kBq m−3 and 144 Bq m−3. From the activity concentrations, absorbed gamma dose rate in outdoor air (D), annual effective dose from external exposure (EE), annual effective dose from inhalation of radon (EI), and excess lifetime cancer risk (ELCR) were estimated in order to assess radiolo...
Keywords: 13. Climate action